Challenges, Trends and Interdisciplinary Perspectives in Musicology: An Interview with Francesco Finocchiaro - Cristina Eleonora PASCU (Studia Universitatis Babeş-Bolyai. Musica)
The interview with Francesco Finocchiaro offers a critical examination of contemporary musicology, addressing its evolving paradigms, methodological developments, and interdisciplinary intersections. In light of the rapid turnover of theoretical frameworks and the influence of dominant academic institutions, this discussion provides an analytical perspective on the forces shaping musicological inquiry today. Finocchiaro questions the balance between textual and contextual approaches, the potential risks of detaching the discipline from its core subject, and the systemic pressures associated with scholarly productivity. His research on silent film music serves as a compelling case study in interdisciplinary scholarship, illustrating the intersections between historical musicology, media studies, and cultural analysis. In addition, his reflections on public musicology underscore the necessity of bridging academic research with wider audiences, fostering broader engagement beyond institutional boundaries. Through these perspectives, the interview emphasizes the importance of mentorship, critical engagement, and adaptive methodologies in sustaining a rigorous and reflective approach to musicological scholarship.